Rooftop Photovoltaic for Residential Electricity Self-Sufficiency: Assessing Potential Benefits in Major Japanese Cities - Samuel Matthew G. Dumlao; Chuyue Yan; Seiichi Ogata (Urban Science)
Rooftop photovoltaic (RTPV) systems have the potential to significantly boost residential electricity self-sufficiency in urban areas. However, estimating the self-sufficiency potential of each city is challenging due to the trade-off between target accuracy and data availability, which limits the scalability of existing methods. This study aims to evaluate the potential of RTPV systems to enhance residential electricity self-sufficiency in major Japanese cities. The self-sufficiency analysis employs a balanced approach using statistical data to estimate RTPV and battery storage capacity in detached houses and hourly simulations to capture supply–demand variations. To project the penetration rate, a logistic curve is utilized to estimate the timeline for achieving a 100% installation rate in detached houses. The analysis reveals that RTPV systems could supply approximately 40% of the residential electricity demand in major cities, with some achieving self-sufficiency rates exceeding 65%. Densely populated cities like Tokyo, Osaka, and Kawasaki may only meet a quarter of their demand due to higher energy requirements. Including older detached houses in RTPV deployment boosted self-sufficiency by an average of 11.77%, with cities like Nagoya, Kyoto, and Kitakyushu achieving increases of 15–20%. Battery storage plays a critical role in enhancing self-sufficiency and reducing energy curtailment. Logistic curve projections suggest that most cities are unlikely to reach 100% RTPV penetration before 2050, though leading cities could achieve 75% penetration by then due to favorable growth rates. These findings reveal that while RTPV has substantial potential to improve residential electricity self-sufficiency, additional efforts are necessary to accelerate adoption. Further research is needed to refine capacity estimates, explore the socioeconomic and political context of the cities, and examine alternative pathways for cities like Tokyo, Osaka, and Kawasaki.